Self-reported summarizing and paraphrasing difficulties in L2 writing contexts: Some pedagogical interventions - Flores, Eden Regala; Lopez, Michelle (Universitas Pendidikan Indonesia, 2019)
The utility of paraphrasing and summarizing is key to effective academic writing. Both require that students have a good grasp of the source material not only in terms of understanding, analyzing, synthesizing, and evaluating the information found in the sources, but also in terms of selecting information, organizing, drafting, and revising their papers. Although several studies have identified L2 students’ difficulties when utilizing paraphrasing and summarizing, this paper examines the cognitive and metacognitive aspects of these complex activities from the students’ eyes. With essays from 120 freshman undergraduate students from a private university in Manila, this study qualitatively determined their reported difficulties when paraphrasing and summarizing, and the areas of improvements in these skills. Participant students identified four major areas of concern: 1) lack of proficiency in English, 2) poor reading comprehension skills, 3) lack of vocabulary and 4) lack of or poor documentation skills. Findings of this study provide grounds for presentation of pedagogical interventions/classroom instructions to address these students’ reported difficulties.